Pengaruh Model Pembelajaran Numbered Head Together (NHT) Berbasis Realistik Terhadap Hasil Belajar Siswa. - Fitri Kurniasari (IKIP PGRI Bojonegoro, 2014)
Effects of Numbered Head Together (NHT) Learning Model Based on Realistic towards Student Achievement. This study was aim at proving whether Numbered Head Together (NHT) learning model based on realistic towards students’ learning outcomes of statistics topic at the seventh graders of MTs Mujahideen Sambong in the academic year of 2012/2013. The population in this study was all students of the second semester students of class VII in MTs Mujahideen Sambong in the academic year of 2012/2013. Sampling was done by cluster random sampling that was selected two classes VIIB and VIIC. From the results of the study, it can be concluded that Numbered Head Together (NHT) learning model based on realistic towards students’ learning outcomes of statistics topic at the seventh graders of MTs Mujahideen Sambong in the academic year of 2012/2013.Keywords: Models of Learning Numbered Head Together (NHT), Realistic, Conventional, Learning Outcomes.